Assessment of Marrubium vulgare hydro-alcoholic extract’s biological activities - Mulondo, Samuel; Kimbugwe, Muzamiru; Lassami, Afaf; Chelghoum, Hayet (Université of Eloued-جامعة الوادي, 2023)
Marrubium vulgare is a tall, robust herbaceous perennial plant originating from Asia and Mediterranean and currently distributed throughout North, South America, Europe, Mediterranean and west Asia. M.vulgare thrives in any type of the soil but it prefers light calcareous, dry soils where it is sunny and warm at an altitude between 1500 –2400 m. This plant is becoming increasingly important because it is currently cultivated in different countries to be used as a source of medicine and food flavors. Also,it has more than 54 different phytocompounds such as polyphenols, monoterpenes, diterpenes and essential oils. Marrubin was the first isolated diterpenes and it’s characterized as the chemotaxonomic marker for the genus Marrubium. According to different studies, these compounds are responsible for antioxidant, antimicrobial, antifungal, analgesic, and anti-inflammatory, wound healing and anthelmintic activities. Due to these biological activities, hydroalcoholic extracts of Marrubim vulgare have been exploited for their therapeutic nature by traditional healers to cure several illnesses in Algeria. This review is to assess the different studies of hydroalcoholic extracts of Marrubium vulgare for different biological activities.
Keywords: Marrubium vulgare, hydro-alcoholic extract, biological activities